Preparation method of lithium manganese iron phosphate material

By mixing ferromanganese oxalate with lithium source, carbon source and dopant, lithium manganese phosphate material with high compaction density and rate performance is prepared, which solves the problems of low compaction density and poor rate performance of traditional LMFP materials, and achieves higher energy density.

CN119551649APending Publication Date: 2025-03-04ZIJIN MINING GROUP CO LTD +1

Patent Information

Application Number
CN202411761879.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The low compaction density and poor rate performance of traditional lithium manganese iron phosphate (LMFP) cathode materials limit their energy density.

Method used

Two types of manganese oxalate - carbon-free coating and carbon coating are used to mix with lithium source, carbon source, phosphorus source and dopant respectively, and precursor A and precursor B are obtained by spray drying, mixed and sintered under an inert atmosphere to achieve independent grading and improve compaction density and rate performance.

Benefits of technology

On the premise of ensuring high specific capacity, high compaction density and rate performance are achieved, solving the problem that the energy density of traditional LMFP materials cannot be exerted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551649A_ABST
    Figure CN119551649A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a lithium manganese iron phosphate material, and relates to the technical field of positive electrode materials. The preparation method of the lithium manganese iron phosphate material comprises the following steps: mixing a first raw material component consisting of ferromanganese oxalate, a first lithium source, a first phosphorus source, a first carbon source and a first doping agent, adding deionized water, grinding, and then carrying out spray drying to obtain a precursor A; mixing a second raw material component consisting of carbon-coated ferromanganese oxalate, a second lithium source, a second phosphorus source, a second carbon source and a second doping agent, adding deionized water, grinding, and performing spray drying to obtain a precursor B; and uniformly mixing the precursor A and the precursor B, sintering in an inert atmosphere, and crushing to obtain the lithium manganese iron phosphate material. According to the lithium manganese iron phosphate material, on the premise of ensuring high specific capacity, relatively high compaction density and relatively high rate capability are realized at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of positive electrode materials and relates to a method for preparing lithium manganese iron phosphate material. Background Art

[0002] The energy density of lithium iron phosphate LiFePO4 (LFP) cathode material is about 575Wh / kg, which has gradually failed to meet the requirements for higher battery energy density. 2+ Replace with Mn 2+ After that, the obtained lithium manganese phosphate LiMnPO4 (LMP) can obtain a higher energy density (up to 700Wh / kg). However, the electronic conductivity of LMP is one order of magnitude lower than that of LFP. At the same time, LMP also has shortcomings such as poor electrochemical activity and slow kinetics.

[0003] In contrast, Fe 2+ , Mn 2+ coexistence, forming lithium iron manganese phosphate (LiFe x Mn 1-x PO4, LFMP), whose electronic conductivity and Li + The diffusion of LMFP is improved compared with LMP, and good electrochemical properties can be obtained. In addition, LMFP has good safety and economy, so it is expected to become an upgraded product of LFP. However, the traditional LMFP positive electrode material has low compaction density and poor rate performance, which limits its energy density and limits its practical application. Chinese patent CN118771342A solves the problem of low compaction density and small discharge specific capacity of traditional LMFP positive electrode materials, which limits their energy density, by adjusting (Mn+Fe) / P, dopant content and median particle size of slurry during sand milling. However, the preparation process of this technology has many steps and is relatively complicated, and it requires multiple sintering, which has high energy consumption.

[0004] Therefore, it is necessary to propose further improvement methods for LMFP positive electrode materials. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing lithium manganese iron phosphate material.

[0006] The technical solution of the present invention is as follows:

[0007] A method for preparing lithium manganese iron phosphate material comprises the following steps:

[0008] Mixing a first raw material component consisting of ferromanganese oxalate, a first lithium source, a first phosphorus source, a first carbon source and a first dopant, adding deionized water for grinding, and then spray drying to obtain a precursor A;

[0009] A second raw material component consisting of carbon-coated ferromanganese oxalate, a second lithium source, a second phosphorus source, a second carbon source and a second dopant is mixed, deionized water is added for grinding, and then spray-dried to obtain a precursor B;

[0010] The precursor A and the precursor B are mixed evenly, sintered in an inert atmosphere, and then crushed to obtain the lithium manganese iron phosphate material.

[0011] Preferably, the molar ratio of the manganese iron oxalate, the lithium in the first lithium source and the first phosphorus source is 1:1.02-1.05:1.01-1.05; the molar ratio of the carbon-coated manganese iron oxalate, the lithium in the second lithium source and the second phosphorus source is 1:1.02-1.05:1.01-1.05.

[0012] Preferably, the weight proportion of the first carbon source in the first raw material component is 4-8%; the weight proportion of the second carbon source in the second raw material component is 12-18%.

[0013] Preferably, the weight proportion of the first dopant in the first raw material component and the weight proportion of the second dopant in the second raw material component are 500 ppm-6000 ppm respectively.

[0014] Preferably, the first dopant and the second dopant are independently selected from one or a combination of two or more of titanium dioxide, magnesium oxide, calcium oxide, zirconium oxide, copper oxide, aluminum oxide, boron oxide, niobium pentoxide and vanadium pentoxide.

[0015] Preferably, the D50 particle size of the precursor A and the D50 particle size of the precursor B are independently 4-35 μm.

[0016] Preferably, the D50 particle size of the precursor A is not less than the D50 particle size of the precursor B.

[0017] More preferably, the D50 particle size of the precursor A is not less than 1.5 times the D50 particle size of the precursor B.

[0018] More preferably, the D50 particle size of the precursor A is 15-35 μm.

[0019] Preferably, the weight ratio of the precursor A to the precursor B is 1:1-10.

[0020] The beneficial effects of the present invention are:

[0021] (1) The present invention adopts two types of ferromanganese oxalate - carbon-free and carbon-coated, which are mixed with lithium source, carbon source, phosphorus source and dopant respectively, and the carbon content of the ground mixture is adjusted in a targeted manner, that is, the carbon content of the ferromanganese oxalate slurry without carbon coating is low, and the carbon content of the ferromanganese oxalate slurry with carbon coating is high. Precursors A and B are obtained by spray drying respectively. After mixing and sintering, autonomous grading is achieved in the growth process of the precursor particles, thereby achieving higher compaction density and higher rate performance while ensuring high specific capacity.

[0022] (2) The present invention further prepares precursors A and precursors B with different particle sizes, that is, the D50 particle size of the precursor A with a low carbon content is higher than the D50 particle size of the precursor B with a high carbon content. After mixing and sintering, the two precursor particles with different particle sizes achieve autonomous grading during the sintering growth process, that is, a high-carbon coated material with a majority of small particle sizes and a low-carbon coated material with a minority of large particle sizes are obtained. The obtained lithium manganese iron phosphate has a wide particle size distribution range, thereby achieving better autonomous grading, achieving higher specific capacity, higher compaction density and higher rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The gram capacity of the lithium manganese iron phosphate material of Example 1 at different rates. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further illustrated and described below through specific implementation methods.

[0025] In order to improve the performance of lithium manganese iron phosphate material LMFP, the present invention provides a method for preparing the lithium manganese iron phosphate material, comprising the following steps:

[0026] Mixing a first raw material component consisting of ferromanganese oxalate, a first lithium source, a first phosphorus source, a first carbon source and a first dopant, adding deionized water for grinding, and then spray drying to obtain a precursor A;

[0027] A second raw material component consisting of carbon-coated ferromanganese oxalate, a second lithium source, a second phosphorus source, a second carbon source and a second dopant is mixed, deionized water is added for grinding, and then spray-dried to obtain a precursor B;

[0028] The precursor A and the precursor B are mixed evenly, sintered in an inert atmosphere, and then crushed to obtain lithium manganese iron phosphate material.

[0029] The present invention adopts two kinds of ferromanganese oxalate, namely, carbon-free ferromanganese oxalate and carbon-coated ferromanganese oxalate, which are ground with a lithium source, a phosphorus source, a carbon source and a dopant and dried to obtain precursors respectively. After the two precursors are evenly mixed, sintered and crushed, a lithium iron manganese phosphate material is obtained. The compaction density and rate performance are further improved while maintaining a high energy density of LMFP, thereby solving the problem in the prior art that the LMFP energy density cannot be exerted due to the low compaction density and insufficient rate performance of the LMFP.

[0030] In the present invention, the preparation method of ferromanganese oxalate and carbon-coated ferromanganese oxalate is not particularly limited, and can be prepared according to the preparation methods of the prior art CN107311853A, CN117790727A, etc., or can be prepared according to the following steps S1-S5:

[0031] S1. According to the stoichiometric ratio, weigh ferrous salt (such as ferrous sulfate, ferrous phosphate, ferrous chloride, ferrous oxalate and ferrous acetate, etc.) and manganese salt (such as manganese sulfate, manganese acetate, manganese carbonate, manganese tetraoxide, manganese dioxide and manganese dihydrogen phosphate, etc.), add appropriate amount of deionized water, and add appropriate amount of first complexing agent (such as ascorbic acid, citric acid, sodium citrate, ammonium citrate, etc.), stir ultrasonically to fully dissolve, and obtain a first solution, the concentration of which can be 0.6-1.5 mol / L; the molar ratio of ferrous salt to manganese salt can be 1:1.5-2;

[0032] S2, weighing an appropriate amount of oxalate (such as ammonium oxalate, sodium oxalate and potassium oxalate, etc.) and adding deionized water, adding a certain amount of a second complexing agent (such as ascorbic acid, citric acid, sodium citrate, ammonium citrate, etc.), heating and stirring to fully dissolve it, to obtain a second solution, the concentration of which can be 0.4-1.2 mol / L;

[0033] S3, weighing an appropriate amount of carbon source (such as polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, polymethyl methacrylate, carbon nanotubes and graphene oxide GO, etc.), adding deionized water, heating and stirring to fully dissolve, to obtain a third solution;

[0034] S4. Using deionized water as the reaction base liquid, the first solution and the second solution (the molar ratio of the first solution to the second solution may be 1:1.2-2) are added dropwise into the reaction base liquid at different flow rates, the flow rate of the first solution is controlled to be 0.5-6 mL / min (or further to 3-6 mL / min), and the flow rate of the second solution is controlled to be 0.75-9 mL / min (or further to 4-8 mL / min), and at the same time, an acidic solution (such as oxalic acid, dilute sulfuric acid, dilute hydrochloric acid, nitric acid, etc.) is added dropwise to control the pH value of the reaction system to be 3-5 (or further, pH to be 3.5-4.5), the reaction temperature is adjusted to 30°C-90°C (or further to 30°C-60°C), the stirring speed is 100r / min-300r / min, the aging time is 2.5-10h, and the oxalate manganese iron powder is obtained after washing, suction filtration, and vacuum drying, wherein the drying temperature is 60°C-100°C, and the drying time is 0.5-20h.

[0035] S5. Using the third solution as the reaction base liquid, the first solution and the second solution are added dropwise into the base liquid at different flow rates, the flow rate of the first solution is controlled to be 0.5-6 mL / min (or further to 3-6 mL / min), and the flow rate of the second solution is controlled to be 0.75-9 mL / min (or further to 4-8 mL / min), and at the same time, an acidic solution (such as oxalic acid, dilute sulfuric acid, dilute hydrochloric acid, nitric acid, etc.) is added dropwise to control the pH value of the reaction to be 1-2 (or further, pH to 1.5-2), the reaction temperature is adjusted to 30°C-90°C (or further to 30°C-60°C), the stirring speed is 100r / min-300r / min, and the aging time is 12-20h; washing, filtering, and vacuum drying to obtain carbon-coated ferromanganese oxalate powder, wherein the drying temperature is 60°C-100°C and the drying time is 0.5-20h.

[0036] In the present invention, the first raw material and the second raw material are ground with water (such as sand grinding), and the D50 particle size of the obtained slurry can be 0.1-0.9 μm, or further can be 0.2-0.4 μm. Spray drying can be carried out by two-fluid spray drying or centrifugal spray drying, and the air inlet temperature can be 170°C-220°C, preferably 180°C-200°C; the air outlet temperature can be 80°C-100°C, preferably 85°C-90°C; the feed rate can be 10-50 mL / min, preferably 15-30 mL / min.

[0037] In the present invention, the inert atmosphere can be one of argon, nitrogen and helium, preferably nitrogen. The sintering conditions can be: temperature of 650°C-800°C, preferably 700°C-780°C, time of 4-12h, preferably 6-10h, heating rate of 1.5-5°C / min, preferably 1.5-3°C / min. The pulverization is performed by air flow mill, the grinding gas pressure is 0.2-0.6Mpa, preferably 0.45-0.55Mpa, the feeding frequency is 10-50Hz, preferably 15-25Hz, the classifying wheel motor frequency is 160-250Hz, preferably 180-220Hz, and the grinding body pressure is -1 to -10kPa, preferably -6 to -9kPa.

[0038] In a preferred embodiment of the present invention, the molar ratio of ferromanganese oxalate, lithium in the first lithium source and the first phosphorus source is 1:1.02-1.05:1.01-1.05; the molar ratio of carbon-coated ferromanganese oxalate, lithium in the second lithium source and the second phosphorus source is 1:1.02-1.05:1.01-1.05. For example, the molar ratio of ferromanganese oxalate, lithium in the first lithium source and the first phosphorus source can be any value of 1:1.02:1.01, 1:1.02:1.03, 1:1.02:1.05, 1:1.03:1.01, 1:1.03:1.03, 1:1.03:1.04, 1:1.03:1.05, 1:1.05:1.01, 1:1.05:1.03, 1:1.05:1.05, etc., without special restrictions. ; The molar ratio of carbon-coated ferromanganese oxalate, lithium in the second lithium source, and the second phosphorus source can be any value in 1:1.02:1.01, 1:1.02:1.03, 1:1.02:1.05, 1:1.03:1.01, 1:1.03:1.03, 1:1.03:1.04, 1:1.03:1.05, 1:1.05:1.01, 1:1.05:1.03, 1:1.05:1.05, etc., without special restrictions. The first lithium source and the second lithium source can be at least one of lithium dihydrogen phosphate, lithium carbonate, lithium acetate, lithium oxalate and lithium hydroxide, preferably lithium carbonate and lithium dihydrogen phosphate. In the above molar ratio of the present invention, the lithium in the first lithium source and the lithium in the second lithium source refer to the lithium molar amount in the first lithium source and the second lithium source, such as 2 mol of lithium in 1 mol of lithium carbonate. The first phosphorus source and the second phosphorus source can be at least one of ammonium hydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and lithium dihydrogen phosphate, respectively, preferably ammonium dihydrogen phosphate.

[0039] In a preferred embodiment of the present invention, the weight proportion of the first carbon source in the first raw material component is 4-8%, for example, the weight proportion can be any value of 4%, 5%, 6%, 7%, 8%, etc., without special restrictions; the weight proportion of the second carbon source in the second raw material component is 12-18%, for example, the weight proportion can be any value of 12%, 13%, 14%, 15%, 16%, 17%, 18%, etc., without special restrictions. The first carbon source and the second carbon source can be at least one of glucose, sucrose, citric acid, polyethylene glycol, polyvinyl pyrrolidone and carbon nanotubes, preferably glucose and polyethylene glycol. In the present invention, when preparing ferromanganese oxalate slurry and carbon-coated ferromanganese oxalate, the contents of the first carbon source and the second carbon source are adjusted to be different. The carbon source content in the carbon-free ferromanganese oxalate slurry is lower, and the carbon source content in the carbon-coated ferromanganese oxalate slurry is higher. The obtained precursors A and precursor B have different carbon contents, the carbon content in precursor A is low, and the carbon content in precursor B is high.

[0040] In a preferred embodiment of the present invention, the weight ratio of the first dopant in the first raw material component and the weight ratio of the second dopant in the second raw material component are independently 500ppm-6000ppm. For example, the weight ratio can be independently 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, etc., without any particular limitation. More preferably, the weight ratio of the first dopant in the first raw material component and the weight ratio of the second dopant in the second raw material component can be independently 2000-4000ppm.

[0041] In a preferred embodiment of the present invention, the first dopant and the second dopant are independently selected from one or a combination of two or more of titanium dioxide, magnesium oxide, calcium oxide, zirconium oxide, copper oxide, aluminum oxide, boron oxide, niobium pentoxide and vanadium pentoxide. Preferably, the first dopant and the second dopant can be independently one or more of titanium dioxide, magnesium oxide, niobium pentoxide and vanadium pentoxide.

[0042] The D50 particle size of the precursor A and the D50 particle size of the precursor B are not suitable if they are too large or too small. If they are too large, the packing density of the obtained lithium iron manganese phosphate material will be insufficient. If they are too small, the precursor particles are easy to aggregate and grow during the sintering process, resulting in excessively large particles of the lithium iron manganese phosphate material. In a preferred embodiment of the present invention, the D50 particle size of the precursor A and the D50 particle size of the precursor B are 4-35 μm alone. For example, the D50 particle size of the precursor A and the D50 particle size of the precursor B can be 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 23 μm, 25 μm, 27 μm, 30 μm, 32 μm, 34 μm, 35 μm, etc., without any special restrictions.

[0043] In a preferred embodiment of the present invention, the D50 particle size of precursor A is not less than the D50 particle size of precursor B, and precursor A and precursor B can undergo autonomous grading during the sintering process, thereby obtaining a lithium iron manganese phosphate material with a higher stacking density, and the lithium iron manganese phosphate material has better rate performance and specific capacity performance.

[0044] More preferably, the D50 particle size of precursor A is not less than 1.5 times the D50 particle size of precursor B. For example, the D50 particle size of precursor A can be 1.5 times, 1.6 times, 1.7 times, 1.8 times, 1.9 times, 2 times, 2.1 times, 2.2 times, 2.3 times, 2.4 times, 2.5 times, etc., of the D50 particle size of precursor B. For example, if the D50 particle size of precursor A is 30 μm, the D50 particle size of precursor B can be 20 μm, 18 μm, 15 μm, 12 μm, 10 μm, etc.; for example, if the D50 particle size of precursor A is 20 μm, the D50 particle size of precursor B can be 13 μm, 12 μm, 10 μm, 8 μm, 6 μm, etc.

[0045] In a preferred embodiment of the present invention, the D50 particle size of the precursor A is 15-35 μm. For example, the D50 particle size of the precursor A can be any value of 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 27 μm, 30 μm, 32 μm, 35 μm, etc., without any particular limitation.

[0046] In a preferred embodiment of the present invention, the weight ratio of precursor A to precursor B is 1:1-10. For example, the weight ratio can be any value of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc., without any particular limitation.

[0047] The lithium manganese iron phosphate material of the present invention can be used as a positive electrode material for lithium ion batteries, and has the characteristics of high compaction density, high rate performance, etc. while ensuring high specific capacity.

[0048] The technical solution of the present invention is further described and illustrated according to various embodiments below.

[0049] The preparation methods of ferromanganese oxalate (labeled as ferromanganese oxalate A) and carbon-coated ferromanganese oxalate (labeled as ferromanganese oxalate B) in the following examples and comparative examples are as follows:

[0050] Step 1: According to a molar ratio of 6:4, 1220 g of manganese sulfate monohydrate and 1330 g of ferrous sulfate heptahydrate are weighed and put into deionized water, and 13 g of citric acid monohydrate is added, and ultrasonically dissolved to obtain a first solution with a concentration of 0.6 mol / L.

[0051] Step 2: weigh 2100 g of ammonium oxalate and 130 g of citric acid monohydrate, add them into deionized water, heat and stir to dissolve, and obtain a second solution with a concentration of 0.8 mol / L.

[0052] Step 3: weigh 500 ml of GO dispersion with a concentration of 10 mg / ml, stir and disperse, and obtain a third solution containing a carbon source.

[0053] Step 4: add the first solution at 60 ml / min and the second solution at 80 ml / min to 500 ml of deionized water reaction base liquid, add oxalic acid to adjust the pH of the reaction to 4, stir at 180 r / min, and keep at 50°C. After the first solution and the second solution are added dropwise, age for 5 hours at 50°C to obtain a suspension of ferromanganese oxalate. Use deionized water to filter and wash repeatedly, and vacuum dry the filter cake at 60°C for 10 hours to obtain ferromanganese oxalate A.

[0054] Step 5: Using the third solution as the reaction base liquid, adding the first solution at 60 ml / min and the second solution at 80 ml / min to the reaction base liquid, adding oxalic acid to adjust the pH of the reaction to 2, stirring at 180 r / min, and the temperature at 50°C. After the first solution and the second solution are added dropwise, the aging time is 16 hours at 50°C to obtain a suspension of ferromanganese oxalate. Deionized water is used for repeated suction filtration and washing, and the filter cake is vacuum dried at 60°C for 10 hours to obtain ferromanganese oxalate B.

[0055] Example 1

[0056] 420 g of lithium carbonate, 1992 g of manganese iron oxalate A, 1303 g of ammonium dihydrogen phosphate, 4.5 g of titanium dioxide, 0.8 g of niobium pentoxide, 1.5 g of magnesium oxide, 118 g of glucose and 177 g of polyethylene glycol were weighed respectively, added with deionized water, sand-milled and obtained slurry A.

[0057] 420 g of lithium carbonate, 1992 g of manganese iron oxalate B, 1303 g of ammonium dihydrogen phosphate, 4.5 g of titanium dioxide, 0.8 g of niobium pentoxide, 1.5 g of magnesium oxide, 222 g of glucose and 333 g of polyethylene glycol were weighed respectively, added with deionized water, sand-milled and obtained slurry B.

[0058] By using different spray drying parameters, the D50 particle sizes of precursor A and precursor B were 30 μm and 15 μm respectively.

[0059] Precursor A and precursor B were fully mixed in a weight ratio of 3:7, and then heated to 780° C. and sintered for 8 h under a nitrogen atmosphere to obtain sintered lithium manganese iron phosphate powder.

[0060] The sintered lithium iron manganese phosphate powder was pulverized by air jet mill, the grinding air pressure was 0.5 MPa, the classifying wheel motor frequency was 200 Hz, the feeding frequency was 25 Hz, and the mill body pressure was -8 kPa to obtain lithium iron manganese phosphate material.

[0061] Example 2

[0062] The difference between this embodiment and embodiment 1 is that in embodiment 1, the D50 particle size of the precursor B is adjusted from 15 μm to 30 μm. The other steps remain unchanged.

[0063] Example 3

[0064] The difference between this embodiment and embodiment 1 is that in embodiment 1, the D50 particle size of the precursor B is adjusted from 15 μm to 20 μm. The other steps remain unchanged.

[0065] Example 4

[0066] The difference between this embodiment and embodiment 1 is that in embodiment 1, the D50 particle size of the precursor B is adjusted from 15 μm to 10 μm. The other steps remain unchanged.

[0067] Example 5

[0068] The difference between this embodiment and embodiment 1 is that in embodiment 1, the weight ratio of precursor A to precursor B is adjusted from 3:7 to 1:1. The other steps remain unchanged.

[0069] Example 6

[0070] The difference between this embodiment and embodiment 1 is that in embodiment 1, the weight ratio of precursor A to precursor B is adjusted from 3:7 to 1:4. The other steps remain unchanged.

[0071] Example 7

[0072] The difference between this embodiment and embodiment 1 is that in embodiment 1, the weight ratio of precursor A to precursor B is adjusted from 3:7 to 1:8. The other steps remain unchanged.

[0073] Example 8

[0074] The difference between this embodiment and embodiment 1 is that in embodiment 1, the D50 particle size of precursor A is adjusted from 30 μm to 20 μm, the D50 particle size of precursor B is adjusted from 15 μm to 5 μm, and the weight ratio of precursor A to precursor B is 1:1. The other steps remain unchanged.

[0075] Example 9

[0076] The difference between this embodiment and embodiment 1 is that the weight ratio of precursor A to precursor B is adjusted from 1:1 to 7:3. The other steps remain unchanged.

[0077] Comparative Example 1

[0078] The difference between this comparative example and Example 1 is that in Example 1, the sintered lithium iron manganese phosphate powder is obtained by sintering the precursor A, that is, no precursor B is added. The remaining steps remain unchanged.

[0079] Comparative Example 2

[0080] The difference between this comparative example and Example 1 is that in Example 1, the sintered lithium iron manganese phosphate powder is obtained by sintering the precursor B, that is, the precursor A is not added. The other steps remain unchanged.

[0081] Comparative Example 3

[0082] The difference between this comparative example and Example 1 is that in Example 1, the D50 particle size of the precursor A is adjusted from 30 μm to 45 μm, and the D50 particle size of the precursor A is adjusted from 15 μm to 40 μm. The other steps remain unchanged.

[0083] Comparative Example 4

[0084] The difference between this comparative example and Example 1 is that in Example 1, the D50 particle size of the precursor A is adjusted from 30 μm to 3 μm, and the D50 particle size of the precursor A is adjusted from 15 μm to 3 μm. The other steps remain unchanged.

[0085] Performance Testing

[0086] The metal lithium sheet was used as the negative electrode, and the lithium iron manganese phosphate materials of Examples 1-9 and Comparative Examples 1-4 prepared by the above method were assembled into a half-cell as the positive electrode for electrochemical performance testing. Specifically, N-methyl-2-pyrrolidone (NMP) was used as a solvent, lithium iron manganese phosphate, Super-P carbon black, and PVDF were weighed and mixed in a mass ratio of 8:1:1, and then coated on aluminum foil, and dried at 110°C for 2 hours and then transferred to a vacuum oven at 110°C for 2 hours. After die-cutting and punching, the positive electrode sheet was obtained, and assembled into a CR2032 button battery in a glove box under argon protection. The battery was tested on a Xinwei constant temperature 26°C electrochemical instrument, with a charge and discharge interval of 2.5V-4.5V, 0.1C charge and discharge activation for 3 cycles, and 1C and 4C were used for constant current and constant voltage charging and discharging. The performance results are shown in Table 1.

[0087] Table 1

[0088]

[0089] The data results in Table 1 above show that the lithium manganese iron phosphate material of the present invention has a high compaction density, specific capacity and rate performance, and the compaction density is greater than 2.35g / cm 3 , 1C gram capacity is not less than 150mAh / g, 4C gram capacity is not less than 140mAh / g, showing good rate performance, and when the D50 particle size of precursor A and precursor B forms a graded distribution, the lithium manganese iron phosphate material has better performance.

[0090] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing lithium manganese iron phosphate material, characterized in that: The steps include: Mixing a first raw material component consisting of ferromanganese oxalate, a first lithium source, a first phosphorus source, a first carbon source and a first dopant, adding deionized water for grinding, and then spray drying to obtain a precursor A; A second raw material component consisting of carbon-coated ferromanganese oxalate, a second lithium source, a second phosphorus source, a second carbon source and a second dopant is mixed, deionized water is added for grinding, and then spray-dried to obtain a precursor B; The precursor A and the precursor B are mixed evenly, sintered in an inert atmosphere, and then crushed to obtain the lithium manganese iron phosphate material.

2. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The molar ratio of the manganese iron oxalate, the lithium in the first lithium source and the first phosphorus source is 1:1.02-1.05:1.01-1.05; the molar ratio of the carbon-coated manganese iron oxalate, the lithium in the second lithium source and the second phosphorus source is 1:1.02-1.05:1.01-1.

05.

3. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The weight proportion of the first carbon source in the first raw material component is 4-8%; the weight proportion of the second carbon source in the second raw material component is 12-18%.

4. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The weight proportion of the first dopant in the first raw material component and the weight proportion of the second dopant in the second raw material component are 500 ppm-6000 ppm respectively.

5. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The first dopant and the second dopant are independently selected from one or a combination of two or more of titanium dioxide, magnesium oxide, calcium oxide, zirconium oxide, copper oxide, aluminum oxide, boron oxide, niobium pentoxide and vanadium pentoxide.

6. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The D50 particle size of the precursor A and the D50 particle size of the precursor B are independently 4-35 μm.

7. The method for preparing lithium iron manganese phosphate material according to claim 6, characterized in that: The D50 particle size of the precursor A is not less than the D50 particle size of the precursor B.

8. The method for preparing lithium iron manganese phosphate material according to claim 7, characterized in that: The D50 particle size of the precursor A is not less than 1.5 times the D50 particle size of the precursor B.

9. The method for preparing lithium iron manganese phosphate material according to claim 7, characterized in that: The D50 particle size of the precursor A is 15-35 μm.

10. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The weight ratio of the precursor A to the precursor B is 1:1-10.

Citation Information

Patent Citations

  • Method for synthesizing battery-grade ferromanganese oxalate

    CN107311853A

  • Ferromanganese oxalate with in-situ carbon-coated core-shell structure and preparation method

    CN117790727A

  • Lithium manganese iron phosphate positive electrode material, preparation method thereof, positive plate and lithium ion battery

    CN118771342A

Cited By

  • Method for preparing lithium manganese iron phosphate material through differential carbon coating

    CN120664515A

  • Preparation method of high-compaction-density lithium manganese iron phosphate positive electrode material

    CN121484065A

  • Preparation method of high-compaction-density lithium iron manganese phosphate positive electrode material

    CN121484065B